Facility layout improvement for continuous production system: a case study in chocolate-based product - Saifurrahman, Anas; Fath, Hamzah; Baasith, Darywan Damar; Aini, Yumna Nur; Wibisono, Arif; Asmara, Sang Norma Lintang (Universitas Gadjah Mada, 2024)
This study explores optimizing Yogyakarta's chocolate production system facility layout to enhance laboratory-scale production to mass production at the UGM Field Research Center laboratory. The laboratory layout was optimized based on expert assessments and the ALDEP algorithm and compared with the current layout using distance-based objective values. Both layouts were compared to highlight the importance of qualitative aspects in determining workstation positions, in addition to quantitative aspects. The distance-based analysis results indicate that the ALDEP layout outperforms the current layout, and the layout was designed with expert assessments, showing the highest efficiency and lowest material handling costs, with an estimated improvement of 23% over the current layout. Although the proposed expert-assessed layout performed worse, it met stakeholder requirements such as safety and ease of observation. Therefore, future research must consider other aspects beyond costs in evaluation metrics to determine the best layout. Although the proposed expert-assessed layout performed worse, it met stakeholder requirements such as safety and ease of observation. Therefore, future research must consider other aspects beyond costs in evaluation metrics to determine the best layout.